The multifaceted RisA regulon of Bordetella pertussis - Coutte, Loïc (Sci Rep, 2016)
The whooping cough agent Bordetella pertussis regulates the production of its virulence factors by the BvgA/S system. Phosphorylated BvgA activates the virulence-activated genes (vags) and represses the expression of the virulence-repressed genes (vrgs) via the activation of the bvgR gene. In modulating conditions, with MgSO(4), the BvgA/S system is inactive, and the vrgs are expressed. Here, we show that the expression of almost all vrgs depends on RisA, another transcriptional regulator. We also show that some vags are surprisingly no longer modulated by MgSO(4) in the risA(−) background. RisA also regulates the expression of other genes, including chemotaxis and flagellar operons, iron-regulated genes, and genes of unknown function, which may or may not be controlled by BvgA/S. We identified RisK as the likely cognate RisA kinase and found that it is important for expression of most, but not all RisA-regulated genes. This was confirmed using the phosphoablative RisAD(60)N and the phosphomimetic RisAD(60)E analogues. Thus the RisA regulon adds a new layer of complexity to B. pertussis virulence gene regulation.